231k views
1 vote
(4 points) Let x

0

=−α;x
1

=0; and x
2

=α. Compute the interpolation polynomial for f(x)=−x
3
using Lagrange Interpolation: p
n

(x)=∑
i=0
n

f
i

l
i

(x)=∑
i=0
n

(f(x
i

)∏
k=0
k

=i


n


x
i

−x
k


x−x
k



)

User Hessam
by
7.4k points

1 Answer

3 votes

Interpolation polynomial for
f(x) = -x^3 is p(x) = -2α^2x..To compute the interpolation polynomial for f(x) = -
x^3using Lagrange Interpolation, we need to find the polynomial that passes through the given points (x0, f(x0)), (x1, f(x1)), and (x2, f(x2)).


Given x0 = -α, x1 = 0, and x2 = α, we can substitute these values into the Lagrange Interpolation formula:
p(x) = f(x0) * L0(x) + f(x1) * L1(x) + f(x2) * L2(x)
where L0(x), L1(x), and L2(x) are the Lagrange basis polynomials.
L0(x) = (x - x1) * (x - x2) / (x0 - x1) * (x0 - x2)
= (x - 0) * (x - α) / (-α - 0) * (-α - α)
=
x * (x - α) / (2α^2)
L1(x) = (x - x0) * (x - x2) / (x1 - x0) * (x1 - x2)
= (x - (-α)) * (x - α) / (0 - (-α)) * (0 - α)
=
(x + α) * (x - α) / (2α^2)
L2(x) = (x - x0) * (x - x1) / (x2 - x0) * (x2 - x1)
= (x - (-α)) * (x - 0) / (α - (-α)) * (α - 0)
=
x * (x + α) / (2α^2)
Substituting these values into the interpolation polynomial formula, we have:
p(x) = f(x0) * L0(x) + f(x1) * L1(x) + f(x2) * L2(x)
=
(-x0^3) * L0(x) + (-x1^3) * L1(x) + (-x2^3) * L2(x)
=
α^3 * L0(x) + 0 * L1(x) + (-α)^3 * L2(x)
=
α^3 * (x * (x - α) / (2α^2)) + (-α)^3 * (x * (x + α) / (2α^2))
=
α^3 * (x^2 - αx) / (2α^2) + (-α)^3 * (x^2 + αx) / (2α^2)
=
α * (x^2 - αx) + (-α) * (x^2 + αx)
=
αx^2 - α^2x - αx^2 - α^2x
=
-2α^2x
Therefore, the interpolation polynomial for
f(x) = -x^3 is p(x) = -2α^2x.

User Frederick Behrends
by
7.4k points